Legends of the sun and moon - Hadley, Eric.; Hadley, Tessa; Nesbitt, Jan (Cambridge [Cambridgeshire] ; Cambridge University Press, 1989)
Twelve traditional tales about the sun and the moon from a variety of cultures.
Keywords: Tales; Folklore; Sun -- Juvenile Literat; Moon -- Legends